Evolution of sequence, structural and functional diversity of the ubiquitous DNA/RNA-binding Alba domain - Jaiganesh Jagadeesh; Shruthi Sridhar Vembar (Scientific Reports)
Abstract The DNA/RNA-binding Alba domain is prevalent across all kingdoms of life. First discovered in archaea, this protein domain has evolved from RNA- to DNA-binding, with a concomitant expansion in the range of cellular processes that it regulates. Despite its widespread presence, the full extent of its sequence, structural, and functional diversity remains unexplored. In this study, we employed iterative searches in PSI-BLAST to identify 15,161 unique Alba domain-containing proteins from the NCBI non-redundant protein database. Sequence similarity network (SSN) analysis clustered them into 13 distinct subgroups, including the archaeal Alba and eukaryotic Rpp20/Pop7 and Rpp25/Pop6 groups, as well as novel fungal and Plasmodium-specific Albas. Sequence and structural conservation analysis of the subgroups indicated high preservation of the dimer interface, with Alba domains from unicellular eukaryotes notably exhibiting structural deviations towards their C-terminal end. Finally, phylogenetic analysis, while supporting SSN clustering, revealed the evolutionary branchpoint at which the eukaryotic Rpp20- and Rpp25-like clades emerged from archaeal Albas, and the subsequent taxonomic lineage-based divergence within each clade. Taken together, this comprehensive analysis enhances our understanding of the evolutionary history of Alba domain-containing proteins across diverse organisms.